Investing in Addressing NCDs and Mental Health Conditions: a Political Choice - Téa E. Collins; Amanda Karapici; Daria Berlina (Annals of Global Health)
Noncommunicable diseases (NCDs) and mental health conditions are responsible for 75% of deaths globally, with the greatest burden in low- and middle-income countries (LMICs). The economic impact of NCDs and mental health conditions on households, health systems, and economies is also staggering. Despite the growing burden of NCDs, the available funding to address these diseases is limited, with less than 2.3% of global health development assistance spent on NCDs. The 2025 United Nations (UN) High-Level Meeting on NCDs will provide a critical opportunity to reaffirm global commitments, enhance political will, and advocate for greater resource mobilization for the prevention and control of NCDs and mental health conditions. Investments will be needed in the strengthening of health systems, integrated models of care, multisectoral action, and a greater focus on vulnerable populations. Increased domestic and international funding will be required for implementation research as well, to ensure sustainable progress toward overcoming context-specific barriers impeding the achievement of Sustainable Development Goals (SDG) target 3.4 on reducing premature mortality from NCDs and improving mental health and well-being. The challenge remains to convert high-level commitments into actionable, measurable strategies and mobilize the resources required to meet these goals, particularly in low-income settings.